Determining the biomechanical changes in lumbar spine among patients with injuries around the knee joint: a systematic review protocol - Raghav, Sumit; Singh, Anshika (International Journal Of Community Medicine And Public Health, 2020)
The knee is one of the body’s more complicated joints and is susceptible to various injuries. A closed kinetic relationship exists between the lumbar spine and knee joint and any dysfunction in knee or lumbar region may result in compensation, joint dysfunction and pain in either one or both the regions. Therefore, the above stated reason highlights the need of analyzing the spine biomechanically. So, that a new physiotherapeutic assessment and treatment approach can be developed in future to prevent permanent adaptive changes in the posture in patients with knee injuries. This systematic review protocol has been conducted by two independent reviewers who searched the articles using electronic search for publications in several databases: Google Scholar, Index Copernicus, JSTOR, PubMed/Medline, ScienceDirect, Scopus and Web of Science. After applying the selection criteria, study papers published between the years 2001 to 2019 have been selected. Studies of human participants of any age having injuries around knee joint have been eligible, and there was no restriction on type of injuries. All the study papers have been analyzed using modified Downs and Black scale and scores have been awarded for the items selected on a 27 point scale. This review has collected secondary data only; hence no ethical approval was required. The results of this review protocol will provide evidence regarding changes in lumbar spine in patients with injuries around knee and this information will be useful in planning for rehabilitation in knee and around knee injury.